Balance, Leg Power, and Motivation as Determinants of Shooting Skills in Islamic High School Football - Supratman Supratman; Andi Ihsan; Benny Badaru (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Goal-shooting skills are crucial in soccer, but student performance is often hampered by a lack of integration between physical and psychological aspects during training. At State Islamic High School 2 Soppeng, the specific determinants that most influence the accuracy and power of extracurricular soccer students have not been thoroughly identified. This study aims to analyze and prove the influence of balance, leg strength, and motivation as the main determinants of shooting skills in extracurricular soccer students at State Islamic High School 2 Soppeng. This study used a quantitative approach with path analysis techniques. The study sample consisted of 30 middle-aged students in the 2025/2026 academic year. Data collection instruments included a balance test, a vertical jump to measure leg strength, a questionnaire for motivation, and a standardized shooting skills test. The results of the inferential analysis showed that all three variables had a significant direct effect on shooting performance (p < 0.05). Leg strength was found to be the most dominant factor (β = 0.418), confirming the importance of muscle explosiveness in generating ball speed. Balance plays a vital role in maintaining body stability when supporting (β = 0.342), while motivation acts as a psychological catalyst that strengthens technical mastery (β = 0.295). Contribution: This study provides practical contributions for coaches and sports teachers in designing a comprehensive training curriculum. The findings recommend a synergy between physical conditioning training (stability and explosive power) with strengthening intrinsic motivation to optimize students' technical potential in soccer.